Methylcellulose-based biopolymer electrolyte in dye-sensitized solar cells / Siti Zulaikha Mohd Yusof - Siti Zulaikha , Mohd Yusof (2019)
Polymer based electrolytes have excellent properties and are not associated with problems encountered with the use of liquid electrolytes (LE). In this work, dyesensitized solar cells (DSSCs) have been fabricated to investigate the possible use of a methylcellulose (MC) based ionic membrane to function as a gel polymer electrolyte (GPE) component of the cells. Before fabricating the DSSCs, the GPEs were optimized. Four polymer electrolyte (PE) systems have been prepared. Lithium bis-oxalato borate (LiBOB) and succinonitrile (SN) have been used as the lithium ion source and plasticizing additive respectively. The first PE system comprises only MC and LiBOB in order to optimize the LiBOB content in the binary complex. The second system comprises MC - LiBOB - SN. SN was added to the highest conducting composition of the MC - LiBOB system. Both MC - LiBOB and MC - LiBOB - SN systems are solid polymer electrolytes (SPEs). These are designated as System I and System 2 espectively. System 3 contains a second salt i.e. tetramethyl ammonium iodide (TMAI) and in System 4, the ionic liquid (IL) butyl methyl imidazolium iodide (BMII) was added. Both Systems 3 and 4 were prepared in gel form and these gel polymer electrolytes (GPEs) were applied in DSSCs. In the preparation of these electrolytes, dimethyl sulfoxide (DMSO) was the solvent. All electrolytes have been characterized using X-ray dimaction (XRD), fourier transform intrared spectroscopy (FTlR) and electrochemical impedance spectroscopy (EIS) techniques. The sample 75 wt.% MC - 25 wt.% LiBOB exhibited the highest conductivity in System I from EIS study. The conductivity was 2. 73 x l 0-6 S cm-1 at room temperature (RT). The highest conducting sample in System 2, 69 wt. % MC - 23 wt. % LiBOB - 8 wt. % SN exhibited a conductivity of 1.30 x 10-5 S cm·1. The effect of gelling the electrolyte with a large amount of DMSO leads to a conductivity that is more than tv.10 orders of magnitude (l.96 mS cm-1) higher and is exhibited by 8.70 wt.% MC - 0.14 wt.% LiBOB - l.Ol wt.% SN - 2.77 wt.% TMAI - 0.35 wt.% h - 87.03 wt.% DMSO. The effect of BMII further increased the RT conductivity by a factor of - l.6 to 3.08 mS cm-1 as exhibited by 8.60 wt.% MC - 0.14 wt.% LiBOB - l.00 wt.% SN - 2.73 wt.% TMAI - 1.10 wt% BMll - 0.45 wt.% h - 85.98 wt% DMSO of System 4. Systems 3 and 4 contained h to create the r-/b- redox couple for the operation of the DSSC. The DSSC with electrolyte containing 95TMAI - 5LiBOB (System 3) exhibited the highest efficiency of 3.52 %. A higher efficiency of 4.63 % was obtained from the DSSC with BMII in the electrolyte. The .fsc was 12.34 mA cm-2 , V oc 0.62 V and FF 0.60. With BMH in the electrolyte, .fsc improved by 52.72 % and efficiency by 31.53 %. All GPE samples were used in DSSC have been characterized using LSV, IPCE, EIS, IMVS and IMPS techniques. Keywords: Biopolymer, methylcellulose, dye-sensitized solar cells, gel polymer electrolyte, ionic conductivity.